ATG8ylation-mediated tonoplast invagination mitigates vacuole damage - Xuanang Zheng; Juncai Ma; Jing Li; Siyu Chen; Jun Luo; Jianxiong Wu; Kaiyan Zhang; Changlian Peng; Yonglun Zeng; Faqiang Li; Byung-Ho Kang; Caiji Gao; et al. (Nature Communications)
Abstract While ATG8ylation, the lipidation of ATG8-family proteins, is canonically linked to double-membrane autophagosome formation, emerging studies demonstrate its non-canonical association with single-membrane organelles. The functional significance of ATG8ylation in these compartments, however, remains unclear. Here, we demonstrate that ionophores rapidly trigger ATG8 conjugation to the vacuolar membrane (tonoplast), a process reliant on the ATG conjugation system rather than the upstream autophagic regulators. Inhibiting reactive oxygen species (ROS) generation or V-ATPase function greatly impedes the targeting of ATG8 to the tonoplast. Intriguingly, the attachment of ATG8 to the tonoplast enhances its invagination and fosters the formation of intraluminal vesicles within vacuoles, which is achieved independently of the ESCRT machinery or cytoskeletal components. The emergence of ATG8-positive vesicles may facilitate the restoration of vacuolar acidification by redirecting proton flow from the vacuole-to-cytoplasm to an intravacuolar direction, which aids in the rapid recovery of plant growth after removal of monensin. Furthermore, under alkaline stress, ATG8 targets the tonoplast and induces vacuolar membrane invagination via a regulatory mechanism similar to that of monensin, indicating that ATG8ylation-mediated vacuolar remodeling represents an adaptive mechanism against environmental alkalinization in plants.